Endothelial Cell Inflammation and Antioxidant Capacity are Associated With 6-Minute Walk Performance in Patients With Symptomatic Peripheral Artery Disease. (May 2018) - Gardner, Andrew W.; Montgomery, Polly S.; Zhao, Yan D.; Ungvari, Zoltan; Csiszar, Anna; Sonntag, William E.
We determined whether 6-minute walk total distance and pain-free distance were associated with circulating biomarkers of antioxidant capacity and inflammation and with cultured endothelial cell inflammation, oxidative stress, and apoptosis in 251 patients with symptomatic peripheral artery disease (PAD). In multivariate analyses, pain-free distance during the 6-minute walk test was negatively associated with dyslipidemia ( P < .001), chronic kidney disease ( P = .004), and transient transfection, nuclear factor κ-Light-Chain-Enhancer of activated B (NF-κB) cultured endothelial cells ( P = .007) and was positively associated with height ( P = .008). Furthermore, total distance walked during the 6-minute walk test was negatively associated with cultured endothelial cell NF-κB ( P < .001), coronary artery disease ( P = .009), and body mass index ( P = .022) and was positively associated with ankle–brachial index ( P < .001), male sex ( P < .001), and hydroxyl radical antioxidant capacity ( P < .001). The 6-minute walk performance in symptomatic patients with PAD was associated with vascular biomarkers, as walking distances were negatively associated with cultured endothelial cell inflammation and positively associated with circulating antioxidant capacity. The clinical implication is that behavioral interventions designed to alleviate endothelial cell inflammation and increase circulating antioxidant capacity, such as exercise and antioxidant intake, may improve ambulation of patients with PAD during submaximal exercise that is typically performed during daily activities.